3D Echocardiography for Rheumatic Heart Disease Analysis: Ready for Prime Time - Vieira, Marcelo Luiz Campos; Branco, Carlos Eduardo de Barros; Gazola, Alessandra Santos Lima; Vieira, Paulo Pinto Alves Campos; Benvenuti, Luiz Alberto; Demarchi, Léa Maria Macruz Ferreira; Gutierrez, Paulo Sampaio; Aiello, Vera Demarchi; Tarasoutchi, Flávio; Sampaio, Roney Orismar (Frontiers in Cardiovascular Medicine, 2021)
Rheumatic heart disease is still a very important health issue worldwide, mainly in underdeveloped countries. Rheumatic heart disease continues to be a very important cause of morbidity and mortality throughout developing countries. Rheumatic heart disease caused by streptococcus from the A group hemolytic streptococcus (Streptococcus pyogenes), keeps position 1 as the most-common cardiovascular disease in young people aged <25 years considering all the continents. Rheumatic heart disease can lead to valvular cardiac aggression as well to carditis. Rheumatic fever aggression leads most commonly to the fusion and thickening of the edges of the cusps and to the fusion, thickening, shortening of the chordae and to calcification of the valves. Valvular commissures can also be deeply compromised leading to severe stenosis. Atria and ventricular remodelling is also common following rheumatic aggression. Mixed valvular agression is more common than isolated valvular disorder. Echocardiography is the most relevant imaging technique to provide not only diagnostic information, but also to enable prognostic data and to present a very important role for the correction of complications after surgical repairs of rheumatic heart valvulopaties. Three dimensional echocardiography provides aditional anatomical and morphofunctional information of utmost importance for patients presenting rheumatic valvopaties. In this sense, three dimensional echocardiography is absolutelly ready for prime time use in rheumatic patients presenting valvulopathies.